Vancomycin loaded alginate/cockle shell powder nanobiocomposite bone scaffold for antibacterial and drug release evaluation - Su, Wen Yuan; Jacinta Santhanam,; Ng, Shiow Fern; B. Hemabarathy Bharatham, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Bacterial infection and biofilm formation is a major concern in orthopaedic implants and bone reconstructive surgery complications that may be addressed with localized drug delivery system. The potential use of a fabricated nanobiocomposite bone scaffold using alginate and nano cockle shell powder for drug release and antibacterial properties was investigated. Vancomycin loaded bone scaffolds were fabricated with 3 and 5 wt% vancomycin, respectively, while a non-drug loaded scaffold was used as controls. The mineralization of the scaffolds using simulated body fluid (SBF) as well as biofilm formation were evaluated using microscopic observations. Drug release study and antimicrobial activity of the eluent from each sampling period was tested for growth inhibition of Staphylococcus aureus and Staphylococcus epidermidis for a period of 21 days. Significant difference of cumulative amount of vancomycin eluted from scaffolds loaded with 5 wt% vancomycin compared to 3 wt% (p<0.05) were noted. Eluent from both groups showed inhibitory effect against bacterial strain tested for 21 days. The findings are further supported with histological observations of reduced biofilm formation by Staphylococcus epidermidis on surface of 5 wt% vancomycin loaded scaffolds compared to control scaffolds. Basic mineralization studies conducted showed no alteration in drug loaded scaffolds characteristics compared to control scaffolds. Findings from this study indicates antibacterial properties can be conferred to the fabricated bone scaffold with successful incorporation of vancomycin with potentials to be used for local drug delivery application.